Where Do Stakeholders Come From? - Alvarez, Sharon A.; Sachs, Sybille (Academy of Management Review, 2023)
Stakeholders self-identify with a firm when they believe they affect and are themselves affected by the actions of a firm. When a firm is already operating, is already implementing a business model, and is already engaging in actions that are more or less consistent with that business model, stakeholders can evaluate whether they are affected or they affect the firm. However, how do stakeholders self-identify in the earliest stages of an entrepreneurial endeavor when a firm has yet to exist and the outcomes of product and service ideas and their effects on stakeholders are unknown? The purpose of this paper is to develop a process model that explains how individuals come to self-identify as stakeholders using the theory of common ground as a foundation (Clark, 1996). Common ground, a theory from the field of linguistics explains how human cooperation emerges and sheds light on how stakeholder self-identification can lead to the emergence of new language, an entrepreneurial endeavor, and product and service ideas. Finally, the paper proposes that how this endeavor is organized is a manifestation of the unique process the stakeholders have gone through.